2014
DOI: 10.1177/0194599814528296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endoscopic Sinus Surgery and Nasal Surgery in Patients with Obstructive Sleep Apnea

Abstract: Although combined nasal and sinus surgery may slightly improve AHI in a certain group of patients, it does not cure OSA or have a significant clinical impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 21 publications
2
43
0
2
Order By: Relevance
“…1 Furthermore, other investigators have shown that patients with CRS and OSA undergoing polypectomy do not reduce their AHI, whereas patients without nasal polyposis did demonstrate significant improvement in AHI scores. 27 Likewise, herein we demonstrate that the difference in polyp status between those with and without OSA did not appear to contribute to the observed difference in sleep dysfunction improvement.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…1 Furthermore, other investigators have shown that patients with CRS and OSA undergoing polypectomy do not reduce their AHI, whereas patients without nasal polyposis did demonstrate significant improvement in AHI scores. 27 Likewise, herein we demonstrate that the difference in polyp status between those with and without OSA did not appear to contribute to the observed difference in sleep dysfunction improvement.…”
Section: Discussionsupporting
confidence: 49%
“…Functional endoscopic sinus surgery has been shown to reduce AHI in patients with moderate to severe OSA, but these improvements were not clinically significant. 27 Likewise, we demonstrate that patients with CRS and OSA do not have significant improvements in sleep quality using the PSQI following FESS. Unfortunately, we did not objectively evaluate nasal obstruction and multilevel airway obstruction in this investigation and are unable to decipher the precise role that FESS plays in improving nasal obstruction as it relates to sleep in our cohort.…”
Section: Discussionmentioning
confidence: 58%
“…More recently, a retrospective study divided CRS patients with comorbid OSA who underwent ESS into three groups: patients with mild OSA, moderate OSA, and severe OSA. Following surgery, patients underwent PSG studies which demonstrated no improvement in objective measures of SQ with no significant changes in NREM stage N2, stage N3, and REM sleep …”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, patients underwent PSG studies which demonstrated no improvement in objective measures of SQ with no significant changes in NREM stage N2, stage N3, and REM sleep. 37 Treatment: Medical vs. Surgical. Typically, the treatment for patients with CRS begins with appropriate medical management.…”
Section: Objective Measures Of Sleep Qualitymentioning
confidence: 99%
“…In this study, patients were grouped, based on their AHI, as mild, moderate, or severe OSA. AHI scores improved in patients with moderate OSA (from 22.3 ± 4.8 to 20.7 ± 8.2, p = 0.023) and severe OSA (from 52.3 ± 21.4 to 43.6 ± 23.9, p = 0.034), while patients with mild OSA did not show significant changes in AHI [57]. Of note, despite statistically significant changes of the AHI, surgery did not completely improve the AHI, which was still well above the cutoff of 5 for normal sleep, reinforcing the idea that in CRS patients with comorbid OSA, sleep apnea needs to be treated with effective therapeutic measures targeting OSA.…”
Section: Osa In Crsmentioning
confidence: 99%